Gender biases in attributions of blame for workplace mistreatment: a video experiment on the effect of perpetrator and target gender - Zedlacher, Eva; Yanagida, Takuya (Frontiers in Psychology, 2023)
Introduction Ambiguous psychological workplace mistreatment such as insulting or ignoring a co-worker might trigger gender bias. This study aims to examine whether female perpetrators receive more moral anger and blame from observers than men. Methods A sample of Austrian workforce members (n = 880, 55.00% women, 44.89% men, 0.11% diverse) responded to standardized videos showing a perpetrator’s angry insult and a perpetrator’s exclusion of a co-worker from lunch. In total, we edited 32 video clips with four female and four male professional actors. We manipulated the following variables: 2 perpetrator gender (male/female) * 2 target gender (male/female) * 2 types of mistreatment (insult/exclusion). Results As hypothesized, linear mixed-effects modeling revealed more moral anger and attributions of intent against female perpetrators than against men. Significant three-way interactions showed that female perpetrators were judged more harshly than men when the target was female and the mistreatment was exclusion. Female targets were blamed less when the perpetrator was female rather than male. Male targets did not evoke attributional biases. Observer gender had no significant interaction with perpetrator or target gender. Discussion Our findings suggest that gender biases in perpetrator-blaming are dependent on target gender and type of mistreatment. The stereotype of women having it out for other women or being “too sensitive” when mistreated by men requires more attention in organizational anti-bias trainings.